Pengembangan Model Mikrosimulasi pada Perlintasan Sebidang Kereta Api pada Jalan Perkotaan dengan PTV VISSIM - Muharam, Fauzan Rizki; Nugroho, Taufiq Suryo; Weningtyas, Widyarini (Department of Civil Engineering, Diponegoro University, 2024)
A level crossing between railways and roads is one of the critical traffic elements in a road network system as it can cause significant delays and long queues, especially when the crossing is part of an urban road network. This study aims to analyze traffic performance at level crossings using a microsimulation approach with the PTV VISSIM software. The model is designed to explicitly simulate the interaction between trains and vehicles by utilizing features such as priority rules, public transport lines, and reduced speed areas, and calibrating it based on field data. This research takes a case study of the level crossing at Jalan Abdul Rahman Saleh – Nurtanio, Bandung City. Data collection was conducted through direct observation via field surveys and data from supporting literature documents. The analysis results indicate that the existing traffic performance is at a Level of Service F, with an average intersection delay exceeding 60 seconds per vehicle. Microsimulation recommends the construction of a grade-separated intersection as a solution to improve traffic performance in the future.